Intravitreal methotrexate in type B lymphoblastic leukemia—Case Report - Maya Naranjo, Maria Isabel; Vallejo López, Sebastián; Mesa Mesa, Sara; Ortiz Pérez, Mónica; López Posada, Mariana; Gaviria Bravo, Martha Lía; González Alviar, María Elena (Frontiers in Oncology, 2023)
Leukemia is a common neoplasia that, in its progress, can have ocular involvement due to direct infiltration or secondary to hematological alterations typical of the disease. These findings are consistent with an involvement of the central nervous system and are thus related to the prognosis. Despite the existing systemic therapies, there needs to be more literature that shows the treatment in the ocular involvement of this disease. A case report of a child with ocular involvement due to treatment-refractory acute lymphoblastic leukemia, successfully managed with intravitreal methotrexate, is presented.